OVIPOSITION OF THE GALL WASP LEPTOCYBE INVASA (HYMENOPTERA: EULOPHIDAE) AND MORPHOLOGICAL CHANGES IN EUCALYPTUS SPP. GENOTYPES SUSCEPTIBLE - Dantas, José Oliveira; Aragão, José Roberto Vieira; Lisi, Claudio Sergio; Silva, Elizamar Círiaco; Anchieta, Renata Lima de; Ribeiro, Genésio Tâmara (Floresta, 2021)
Eucalyptus is grown worldwide for many purposes, as for production of wood, firewood, cellulose and essential oils. Eucalyptus was introduced into Brazil in 1904, and its cultivation has been growing since that time, with about 5.57 million hectares of plantations in 2014. This increase in plantations has favored the native insect populations, some insects have become pests, while other exotic insect pests were introduced such as the gall wasp (Leptocybe invasa), which oviposits in the midrib of leaves, petiole, and in young shoots, causing the formation of galls which compromise the normal growth of plants. In order to evaluate the morphological changes in genotypes of Eucalyptus spp., caused by the galls formation, the anatomical alterations qualitative and quantitatively of the vascular bundles were studied. The results showed that oviposition occurs in the four genotypes studied, but the genotype 1404 is resistant to gall formation, while the susceptibility is low in genotype 1277, medium in genotype 1724 and very high in genotype 1262. The vascular bundles and parenchyma cells in the leaves and petioles were disorganized. The emergence of adult insects caused ruptures in vascular, parenchyma and epidermal cells, resulting in necrosis and foliar droughtness.